CHARACTERISTICS OF BRAZILIAN SCIENTIFIC RESEARCH ON DIFFUSION OF INNOVATIONS IN BUSINESS ADMINISTRATION (INMR - Innovation & Management Review, 2018)
The aim of this paper is to analyze the characteristics of Brazilian scientific research in diffusion of innovations in administration. A bibliometric research was conducted with network analysis in scientific papers about diffusion of innovations in Spell database. The papers were analyzed from descriptive, bibliographic, methodologic, results and citation characteristics. The authors concluded that Brazilian publications are coherent with the international research considering the adoption of diffusion of innovations frameworks. Still, it has a trait of considering government support in diffusion frameworks, an absent parameter in the original frameworks; therefore, representing a development potential for diffusion of innovations researchers in Brazil.